Designing Ecosophic Generations: An Experiment with Eco Pedagogical Model: Comparing the Effectiveness of Ecopedagogical Model and Critical Pedagogy in Developing Ecosophy in Secondary School Students (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Ecosophy is a philosophy of ecological harmony and an approach to the environment which emphasize the importance of action and individual belief in the preservation of planet. The ignorance about the principles of organization of nature and the inability to manage life without annoying the equilibrium of nature is the prime reason for the ecological devastation found today which is unprecedented in the history of the blue planet. People equipped with this philosophy will lead an ecologically conscious life without disturbing the organization of nature. The investigators prepared a teaching model, Ecopedagogical Model to develop the ecological conscience of secondary school students based on the principles and values of Earth Charter (1992). The study aims to compare the effectiveness of prevailing teaching method which follows the ideology of Critical Pedagogy and the new Ecopedagogical Model based on Ecopedagogy which is an extension of Critical Pedagogy. Pre-test – post-test nonequivalent two group design from quasi experimental designs was selected for the study. Two 8th standard intact classrooms were selected as experimental and control groups with 33 and 34 students respectively in each group. 30 lessons from biology curriculum were executed in both classes but in different methods. The prepared Inventory on Ecosophy was used as pre-test and post-test in both groups to find the difference. The statistical analysis canvassed the Ecopedagogical Model is more effective in the development of ecosophy among secondary school students when compared to prevailing method of teaching.